Correction: Antimicrobial peptide based magnetic recognition elements and Au@Ag-GO SERS tags with stable internal standards: a three in one biosensor for isolation, discrimination and killing of multiple bacteria in whole blood. Issue 2 (12th December 2018) - Yuan, Kaisong; Mei, Qingsong; Guo, Xinjie; Xu, Youwei; Yang, Danting; Sánchez, Beatriz Jurado; Sheng, Bingbing; Liu, Chusheng; Hu, Ziwei; Yu, Guangchao; Ma, Hongming; Gao, Hao; et al.
Abstract : Correction for 'Antimicrobial peptide based magnetic recognition elements and Au@Ag-GO SERS tags with stable internal standards: a three in one biosensor for isolation, discrimination and killing of multiple bacteria in whole blood' by Kaisong Yuan et al., Chem. Sci., 2018, DOI: 10.1039/c8sc04637a.